Research on isolation, identification, and determination of suitable conditions for the cultivation of albino Cordyceps militaris SHBTD fruiting bodies - Anh, Dao Ngoc; Chien, Truong Thi; Trang, Do Thi Kim; Tram, Tran Bao; Mai, Nguyen Thi Thanh; Dung, Thai Hanh; Tuan, Tran Van; Tao , Vu Xuan (Vietnam Journal of Biotechnology, 2024)
Cordyceps militaris is a valuable fungus that is well-known in many Asian countries. The fruiting bodies of C. militaris are commonly used in traditional medicine and the production of functional foods. Currently, C. militaris mushrooms are being cultivated on a large scale in Vietnam, yielding the characteristic yellow-orange fruiting bodies typical of C. militaris. In the mushroom cultivation industry, C. militaris is one of the most highly valued species. The yield and quality of the fruiting bodies are greatly dependant on the strain source. Therefore, the search for new strains of C. militaris with high productivity, quality, and uniqueness is always of interest to scientists. This study has isolated and identified the albino strain C. militaris SHBTD based on morphological characteristics and the rDNA ITS region gene sequence. The optimal conditions for fruiting body formation of the SHBTD strain are MT6 medium, a temperature of 22°C, a humidity of 90%, a light intensity of 500 lux (12 hours/day), and 65 days of cultivation. Additionally, this study determined that the albino strain C. militaris SHBDT carrying the single Mating-type (MAT) gene (MAT1-1-1), could provide stable yield and quality of fruiting bodies over 5 consecutive cultivation generations. The obtained results demonstrate the potential applications of the C. militaris SHBTD in the industrial-scale production of unique and high-value mushroom products.